Smart distribution system volt/VAR control using distributed intelligence and wireless communication. Issue 4 (1st March 2015) - Ibrahim, Michael; Salama, Magdy M.A.
Abstract : This study presents a smart volt/VAR control (VVC) technique for smart distribution systems, which is designed to be integrated into a distributed real‐time analysis and control framework implemented with the use of multiple processing units equipped with wireless communication transceivers. The distributed processing units collaborate to perform power flow analysis based on smart meter measurements for controlling and coordinating the switched capacitor banks and voltage‐regulating transformers. The objective is to maintain acceptable voltage levels along the distribution feeder, minimise system losses, and limit the number of switching operations. GNU‐Octave simulations are employed as a means of evaluating the performance of the proposed smart VVC technique with respect to loss reduction and number of switching operations. The network simulator ns‐3 is used to simulate the distributed processing units that execute the proposed smart VVC technique. Worldwide interoperability for microwave access (WiMAX) and long‐term evolution (LTE) communication networks are employed in the ns‐3 simulations in order to provide data connectivity among the distributed processing units. The performance of the communication network is evaluated in terms of the execution time of the smart VVC technique, the average packet delay and the average packet delivery ratio.